NOACs only for those who cannot tolerate a VKA: where is the evidence?. Issue 1 (2nd January 2019) - Bhagirath, Vinai C.; Cosyns, Bernard; Eikelboom, John W.
Abstract: The 2016 European Society of Cardiology Guidelines recommend non-vitamin K antagonist oral anticoagulants (NOACs) in preference to vitamin K antagonists (VKA) for stroke prevention in atrial fibrillation. A recent report from the Belgian Healthcare Knowledge Centre (KCE) raised concerns about the results of the phase 3 randomised trials that led to the approval of the NOACs for this indication and concluded that NOACs should only be used for patients who fail or cannot undergo treatment with a vitamin K antagonist because they cannot achieve stable INR values. Evidence from community-based studies suggests that NOACs are often not optimally used; however, our critical review of the randomised trial data provides no support for the concerns raised by the Belgian KCE about the trials. Furthermore, the results of observational studies involving more than 700, 000 participants replicate those of the randomised trials, indicating that the benefits of NOACs seen in the trials can be readily translated to patient care. Due to their superior convenience and safety, NOACs also have the potential to reduce undertreatment of atrial fibrillation patients.